Asphalt Pavement Compaction Control: Relevance of Laboratory and Non-Destructive Testing Methods of Density - Andrius Baltrušaitis; Audrius Vaitkus; Jurgita Židanavičiūtė (The Baltic Journal of Road and Bridge Engineering)
Assurance of asphalt pavement layer compaction, expressed by air voids ratio between field and laboratory bulk density, is one of the main criteria of the asphalt pavement durability. Thus, destructive measures should be applied, and many asphalt samples should be taken on site in order to determine the representative compaction level of constructed pavement. With the fast development of technologies, new methods should be considered for fast, non-destructive and accurate determination of asphalt bulk density on site. As there are quite few non-destructive methods related to asphalt pavement density measurement, there is a need to make comparison of such methods. Currently, when GPR methods are used to determine the density, calibration cores are used in all cases to estimate the unknown or unmeasured variables or conditions that may affect the results of dielectric value measurements. The aim of this study is to develop a regression model that can predict the bulk density of the compacted asphalt layer without coring, using the design values of the bulk density determined in the type tests of asphalt mixtures or other currently used non-destructive testing technologies (in this case PQI and NDG) and GPR measured dielectric constant values.